3D ToF-SIMS imaging of polymer multilayer films using argon cluster sputter depth profiling - Bailey, James; Havelund, Rasmus; Shard, Alexander G.; Gilmore, Ian S.; Alexander, Morgan R.; Sharp, James S.; Scurr, David J. (American Chemical Society, 2015)
ToF-SIMS imaging with argon cluster sputter depth profiling has provided detailed insight into the three-dimensional (3D) chemical composition of a series of polymer multilayer structures. Depths of more than 15 μm were profiled in these samples while maintaining uniform sputter rates. The 3D chemical images provide information regarding the structure of the multilayer systems that could be used to inform future systems manufacturing and development. This also includes measuring the layer homogeneity, thickness, and interface widths. The systems analyzed were spin-cast multilayers comprising alternating polystyrene (PS) and polyvinylpyrrolidone (PVP) layers. These included samples where the PVP and PS layer thickness values were kept constant throughout and samples where the layer thickness was varied as a function of depth in the multilayer. The depth profile data obtained was observed to be superior to that obtained for the same materials using alternative ion sources such as C60 n+. The data closely reflected the “as manufactured” sample specification, exhibiting good agreement with ellipsometry measurements of layer thickness, while also maintaining secondary ion intensities throughout the profiling regime. The unprecedented quality of the data allowed a detailed analysis of the chemical structure of these systems, revealing some minor imperfections within the polymer layers and demonstrating the enhanced capabilities of the argon cluster depth profiling technique.